Percussion solo parts in Rogerio Duprat’s Antinomies I (Per Musi, 2023)
This article aims to analyse the solo percussion parts in Antinomies I, written for chamber orchestra by Brazilian composer Rogério Duprat (1932–2006) in 1962. Characterised by its graphic notation, the composer uses indeterminacy to lead the orchestra into an unconventional paradigm of sound creation. The analysis focuses on the percussionist's range of choices in order to understand how they affect the macro and microstructural elements of the work. There is considerable scope for choices in the percussion part of Antinomies I, which requires the use of "multi-percussion". Eight of the thirty-two circular structures that form the score are percussion solos. It is a significant number, greater than any other individual instrumentalist from the chamber orchestra. These circles form a heterogeneous group with different degrees of indeterminacy whose analysis reveals the interpretive process of transforming a graphic score into percussion sounds.